Question
upstudy study bank question image url

Decompose \( \frac{x^{2}-3}{(x-1)\left(x^{2}+1\right)} \)

Ask by Santiago Mathis. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( \frac{x^{2}-3}{(x-1)(x^{2}+1)} = -\frac{1}{x-1} + \frac{2x+2}{x^{2}+1} \)

Solution

We want to express   (x² – 3) / [(x – 1)(x² + 1)] as a sum of simpler fractions. Since the denominator factors into a linear term (x – 1) and an irreducible quadratic (x² + 1), we write the partial fractions in the form:   A/(x – 1) + (Bx + C)/(x² + 1). Step 1. Write the identity:   (x² – 3)/[(x – 1)(x² + 1)] = A/(x – 1) + (Bx + C)/(x² + 1). Step 2. Clear the fractions by multiplying both sides by (x – 1)(x² + 1):   x² – 3 = A(x² + 1) + (Bx + C)(x – 1). Step 3. Expand the right-hand side:   A(x² + 1) = Ax² + A.   (Bx + C)(x – 1) = Bx² – Bx + Cx – C = Bx² + (C – B)x – C. Thus,   x² – 3 = (A + B)x² + (C – B)x + (A – C). Step 4. Equate coefficients of corresponding powers of x:   Coefficient of x²: A + B = 1.   Coefficient of x:  C – B = 0.   Constant term:   A – C = -3. From C – B = 0, we have C = B. Substitute C = B into A – C = -3:   A – B = -3  → A = B - 3. Then substituting A = B - 3 into A + B = 1:   (B - 3) + B = 1  → 2B - 3 = 1  → 2B = 4  → B = 2. Thus,   A = 2 - 3 = -1,   C = B = 2. Step 5. Write the final decomposition:   (x² – 3)/[(x – 1)(x² + 1)] = -1/(x – 1) + (2x + 2)/(x² + 1). We can also factor the numerator of the second term:   (2x + 2) = 2(x + 1), so another acceptable answer is:   (x² – 3)/[(x – 1)(x² + 1)] = -1/(x – 1) + [2(x + 1)]/(x² + 1). This is the required partial fractions decomposition.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To decompose the given expression \( \frac{x^{2}-3}{(x-1)(x^{2}+1)} \), we can express it in the form: \[ \frac{A}{x-1} + \frac{Bx + C}{x^{2} + 1} \] where \( A \), \( B \), and \( C \) are constants to be determined. Multiply both sides by the denominator \( (x-1)(x^{2}+1) \): \[ x^{2}-3 = A(x^{2}+1) + (Bx + C)(x-1) \] Now, expand the right side: \[ x^{2}-3 = A(x^{2}+1) + (Bx^{2} - Bx + Cx - C) \] \[ = Ax^{2} + A + Bx^{2} + (C-B)x - C \] \[ = (A + B)x^{2} + (C-B)x + (A - C) \] Now we match coefficients from both sides of the equation: 1. For \( x^{2} \): \( A + B = 1 \) 2. For \( x \): \( C - B = 0 \) 3. Constant term: \( A - C = -3 \) Now we solve this system of equations: From \( C - B = 0 \), we have \( C = B \). Substituting \( C = B \) into \( A - C = -3 \): \[ A - B = -3 \quad \text{(1)} \] Now substituting \( C = B \) into \( A + B = 1 \): \[ A + B = 1 \quad \text{(2)} \] Now we can solve these two equations. From equation (2): \[ A = 1 - B \] Substituting this expression for \( A \) into equation (1): \[ 1 - B - B = -3 \] \[ 1 - 2B = -3 \] \[ -2B = -4 \] \[ B = 2 \] Using \( B = 2 \) in equation (2): \[ A + 2 = 1 \implies A = -1 \] And since \( C = B \): \[ C = 2 \] Thus, we have found the values: \[ A = -1, \quad B = 2, \quad C = 2. \] The partial fraction decomposition is: \[ \frac{x^{2}-3}{(x-1)(x^{2}+1)} = \frac{-1}{x-1} + \frac{2x + 2}{x^{2}+1}. \] So the final answer is: \[ \frac{-1}{x-1} + \frac{2x + 2}{x^{2}+1}. \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy